Western Enlightenment and its Impact on Weakening Belief - Mansour, Ruqaiya (Islamic Sciences Journal, 2023)
Western enlightenment is one of the most important terms of a Western character that has been introduced to Islamic societies in one way or another, or as a result of Muslims being influenced by Western civilization. It is a reason for weakening the belief of the members of the Muslim community and by all media means and advanced scientific technique as well. The purpose behind this is to challenge and question the Islamic constants and to seek to distract Muslims from building their future and drowning them in the problems of identity and thought, and that the goal of all of this is to destroy the true Islamic religion from the hands of its members, What is published today is of ideological suspicions, sectarian strife and ideas of atheism. Contemporary Jahiliyyah has claimed at the beginning of the Renaissance that it could turn its back on religion and then continue to practice life in a normal manner without any deficiency or imbalance, claiming that when it gets rid of religion, it would remedy what was in its life of deficiency and imbalance! And slough off that religion that disturbs the peace of life, disrupts its impulse, spreads ignorance, blocks thought, and blocks light from humanity. By experience it has been proven that there is no real source of values and principles other than religion. They said that it is the mind and they said that it is the nature, and they said the human soul, and they said science, and they said philosophy. By departing from religion and common sense, they reached anxiety, madness, loss, confusion, mental illness, nervousness, suicide, alcohol, drugs, crime, decadence and metamorphosis that distort the nature... and moral, intellectual and spiritual decline in all fields of political, economic and social life at the level of individuals, groups and peoples. Given the importance of the matter, it was one of the reasons and reasons for research and the current study. Therefore, this research came tagged: (The Western Enlightenment and its Effect on Weakening the Creed). This study was divided into an introduction and a conclusion, and two sections.